2016
DOI: 10.2337/dc16-1625
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trajectories of Metabolic Control From Childhood to Young Adulthood in Type 1 Diabetes From a Large German/Austrian Registry: A Group-Based Modeling Approach

Abstract: Using a trajectory approach, we determined five distinct longitudinal patterns of glycemic control from childhood to early adulthood. Diabetes self-care, treatment differences, and demographics were related to different HbA courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
124
4
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(144 citation statements)
references
References 37 publications
15
124
4
1
Order By: Relevance
“…A recent study analyzing data from the multicenter diabetes registry Diabetes‐Patienten‐Verlaufsdokumentation (DPV) identified five distinct longitudinal HbA1c trajectories from childhood (8 years) through to young adulthood (19 years) . Although the aim of this DPV study was not to compare injection and pump therapy but to identify trajectories; the results support the findings of our study.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study analyzing data from the multicenter diabetes registry Diabetes‐Patienten‐Verlaufsdokumentation (DPV) identified five distinct longitudinal HbA1c trajectories from childhood (8 years) through to young adulthood (19 years) . Although the aim of this DPV study was not to compare injection and pump therapy but to identify trajectories; the results support the findings of our study.…”
Section: Discussionsupporting
confidence: 85%
“…Crucially, previous reports [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have largely examined individuals with pre-existing type 1 diabetes (i.e. not from the time of diagnosis).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of insulin needed to maintain glycemic control increases in puberty [6] and with longer T1D duration and older age [7]. The DCCT—Epidemiology of Diabetes Interventions and Complications (EDIC) study also demonstrated that increased insulin needs are associated with more T1D complications [8, 9] and weight gain and higher weight status across time in individuals with T1D [1012, 13••] because of the anabolic and lipogenic actions of insulin [14].…”
Section: The Role Of Insulin In Weight Gainmentioning
confidence: 99%